Analisis Kemampuan Membaca, Berpikir, dan Berbicara Peserta Didik Berkebutuhan Khusus di SD Negeri Kalibanteng Kidul 01 Kota Semarang - Sholikha, I’malus; Setyaningrum, Riska; Safitri, Henis Wahyu; Azizah, Wulan Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the reading, thinking, and speaking skills of students with special needs (PDBK) at SD Negeri Kalibanteng Kidul 01 Semarang City in the context of inclusive education. These three aspects are important foundations in the learning process that support students’ cognitive, affective, and psychomotor development. The study used a qualitative approach converted to quantitative based on the assessment indicators of Permendikbud No. 23 of 2016. The results showed that the highest achievement was in the thinking skills aspect, while speaking skills showed the greatest variation between individuals. These differences in ability reflect the uniqueness of each student’s learning style and needs. Therefore, a holistic, adaptive, and differentiated learning strategy is needed to accommodate the potential and challenges faced by each student. These findings contribute to the development of inclusive education policies and support teaching practices that are more responsive to student diversity.